Effect of precipitating factors of acute heart failure on readmission and long‐term mortality. (21st January 2016) - Arrigo, Mattia; Tolppanen, Heli; Sadoune, Malha; Feliot, Elodie; Teixeira, Antonio; Laribi, Said; Plaisance, Patrick; Nouira, Semir; Yilmaz, Mehmet Birhan; Gayat, Etienne; Mebazaa, Alexandre; ,
Abstract: Aims: Acute heart failure (AHF) is one of the leading causes of unscheduled hospitalization and is associated with frequent readmissions and substantial mortality. Precipitating factors of AHF influence short‐term mortality, but their effect on outcome after hospital discharge is unknown. The present study assessed the effect of precipitating factors on readmission and long‐term survival in the overall population and in patients aged 75 years or younger. Methods and results: Patients admitted with AHF ( n  = 755) included in the multicentre cohort 'Biomarcoeurs' were included in the study. Precipitating factors of AHF were classified in four main groups: acute coronary syndrome, atrial fibrillation, acute pulmonary disease and other causes. Hospital readmission during 90 days after discharge and survival at 1 year were analysed. Precipitating factors influenced readmissions and survival. Acute pulmonary disease was associated with fewer readmissions (HR 0.61, 95% confidence interval (CI) 0.37–0.99, P  = 0.049), especially in patients aged 75 years or younger (HR 0.20, 95% CI 0.06–0.63, P  = 0.006), whereas atrial fibrillation (HR 2.23, 95% CI 1.29–3.85, P  = 0.004) and acute coronary syndrome (HR 2.23, 95% CI 1.02–4.86, P  = 0.044) were associated with more readmissions. Patients with acute pulmonary disease at admission showed higher mortality (HR 1.59, 95% CI 1.04–2.43, P  = 0.034), especially in subjects aged 75 years or younger (HR 2.52, 95% CI 1.17–5.41, P  = 0.018). Conclusions: Precipitating factors of AHF substantially influenced outcome after hospitalization. In particular, patients with AHF precipitated by acute pulmonary disease showed fewer readmissions and higher 1 year mortality, especially in patients aged 75 years or younger.